# High School Math Test

16 Questions | Total Attempts: 76  Settings  This test allows you to determine how much high school math you know based on the math topics learned in high school (grades 9-12). The test includes questions from algebra, geometry, trigonometry, pre-calculus, and calculus. The questions get progressively harder, and calculators are not required to solve any question. A TI-84 calculator is recommended. The test is timed, so use your time wisely!

Related Topics
• 1.
Factor x2 - 2x - 24.
• A.

X(x-6)

• B.

X(x-12)

• C.

(x-4)(x-6)

• D.

(x-4)(x+6)

• E.

(x+4)(x-6)

• 2.
Factor 6x2 + 17x + 12.
• A.

(3x+3)(2x+4)

• B.

(2x+3)(3x+4)

• C.

(3x-3)(3x-4)

• D.

(2x+3)(3x+2)

• E.

(2x-3)(3x-2)

• 3.
Solve the system of linear equations:x + 2y = 93x - 4y = - 33
• A.

X = 3, y = -6

• B.

X = 3, y = 6

• C.

X = 2, y = 7

• D.

X = -3, y = 6

• E.

X = 9, y = 12

• 4.
Find the equation for a line that passes through the two points (3,4) and (1,-10).
• A.

Y = 7x - 17

• B.

Y = 7x + 17

• C.

Y = x/7 - 17

• D.

Y = x/7 + 10

• E.

Y = x/7 - 10

• 5.
Find the exterior angle of a heptagon.
• A.

30 degrees

• B.

49 degrees

• C.

51 degrees

• D.

60 degrees

• E.

129 degrees

• 6.
Triangle ABC is similar to DEF. The length of EF is 7 inches, while the length of BC is 5 inches. If the length of AB is 16 inches, what is the length of DE?
• A.

22.4 inches

• B.

23.0 inches

• C.

20.5 inches

• D.

25.3 inches

• E.

19.5 inches

• 7.
Find the volume of a sphere that has a diameter of 5 meters.
• A.

8.3π meters^3

• B.

33π meters^3

• C.

166π meters^3

• D.

20.8π meters^3

• E.

6.7π meters^3

• 8.
Two lines, AB and CD, intersect at point E. If angle AED is 127 degrees, what is angle BED + angle AEC?
• A.

127 degrees

• B.

26.5 degrees

• C.

53 degrees

• D.

106 degrees

• E.

Not enough information is given to solve the problem.

• 9.
Sin(π/3) can be expressed alternatively as
• A.

Sin(π/3) cos(π/6)

• B.

2 sin(π/3) cos(π/6)

• C.

2 sin(π/6) cos(π/6)

• D.

2 sin(π/6)

• E.

None of the above.

• 10.
Tan(π/2) is equal to
• A.

0

• B.

Sqrt(2) / 2

• C.

3 sqrt(2) / 2

• D.

1 / 2

• E.

None of the above.

• 11.
What is the limit of the function y = 1 / (x - 4) as x approaches 4?
• A.

0

• B.

-1/4

• C.

+ infinity

• D.

- infinity

• E.

No limit

• 12.
What is the slope of the tangent line of y = x3 at x = 2?
• A.

M = 4

• B.

M = 12

• C.

M = -1/12

• D.

M = 16

• E.

M = -1/16

• 13.
What is the second derivative of y = 3x5 - 4x4 + 2x2 + 6?
• A.

Y = 20x^3 + 48x^2 + 4

• B.

Y = 60x^3 + 48x^2 - 4

• C.

Y = 12x^4 - 4x^3 + 2x + 2

• D.

Y = 15x^4 - 16x^3 + 4x

• E.

Y = 60x^3 - 48x^2 + 4

• 14.
What is the derivative of y = sin (2x + 5)?
• A.

Cos (2) + 5

• B.

Cos (2x + 5)

• C.

2 cos (2x + 5)

• D.

2 cos (2x) + 5

• E.

-2 cos (2x + 5)

• 15.
Integrate (x+4)2.
• A.

X^3/3 + 4x^2 + 16x + c

• B.

4x^3 + 4x^2 + c

• C.

X^3 - 4x^2 + x + c

• D.

(x + 4)^2 + c

• E.

2(x + 4) + c

• 16.
Integrate 1 / (x2 + 3x + 2).